2020
DOI: 10.1111/ctr.13810
|View full text |Cite
|
Sign up to set email alerts
|

Comparable survival outcome between transplantation from haploidentical donor and matched related donor or unrelated donor for severe aplastic anemia patients aged 40 years and older: A retrospective multicenter cohort study

Abstract: This retrospective multicenter cohort study aimed to compare the outcome of haploidentical hematopoietic stem cell transplantation (HID‐HSCT) with matched sibling donor (MSD) and unrelated donor (URD) transplantation in severe aplastic anemia (SAA) patients 40 years of age and older. With a median follow‐up time of 17.6 months, 85 consecutive patients were enrolled in the study, and the median patient age was 45 years (40, 58). The cumulative engraftment rates of neutrophil and platelet were 98.8 ± 0.0% and 92… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 29 publications
1
10
1
Order By: Relevance
“…In a multicenter study, HID and MSD HSCT demonstrated comparable failure-free survival both as salvage treatments and as upfront treatments (86.8% vs. 80.3% and 85.0% vs. 89.8%) [ 17 , 18 ]. Even for older patients aged 40 years and older, HID might be a feasible alternative option, with comparable OS and FFS rates among HID, MSD, and URD (86.7%, 92.1, 100% and 86.7%, 92.1%, 87.5%) in another study [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a multicenter study, HID and MSD HSCT demonstrated comparable failure-free survival both as salvage treatments and as upfront treatments (86.8% vs. 80.3% and 85.0% vs. 89.8%) [ 17 , 18 ]. Even for older patients aged 40 years and older, HID might be a feasible alternative option, with comparable OS and FFS rates among HID, MSD, and URD (86.7%, 92.1, 100% and 86.7%, 92.1%, 87.5%) in another study [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, 32 records were excluded, and 29 studies met the inclusion criteria. The included studies were divided into two groups (MSCs [31][32][33][34][35][36][37][38]; no MSCs [22,24,25,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]) based on whether they applied the MSCs or not. The selection process is illustrated in Fig.…”
Section: Search Resultsmentioning
confidence: 99%
“…As a result, 32 records were excluded, and 29 studies met the inclusion criteria. The included studies were divided into two groups (MSCs [31][32][33][34][35][36][37][38] ; no MSCs 22,25,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] ) based on whether they applied the MSCs or not. The selection process is illustrated in Fig.…”
Section: Search Resultsmentioning
confidence: 99%